Genomic insights into the taxonomic status and bioactive gene cluster profiling of Bacillus velezensis RVMD2 isolated from desert rock varnish in Ma’an, Jordan - Sulaiman M. Alnaimat; Saqr Abushattal; Saif M. Dmour; Wajdy J. Al-Awaida; Amani M. Ayyash; Khang Wen Goh (PLoS ONE, 2025)
Extreme environments like arid and semi-arid deserts harbor unique microbial diversity, offering rich sources of specialized microbial metabolites. This study explores Bacillus velezensis RVMD2, a strain isolated from rock varnish in the Ma’an Desert, Jordan. The genome was sequenced using the Illumina NextSeq 2000 platform, resulting in a 4,212,579 bp assembly with a GC content of 45.94%. The assembled genome comprises 112 contigs and encodes 4,250 proteins, 77 tRNA genes, and 4 rRNA genes. Phylogenetic analysis of the 16S rRNA gene indicated a 99.84% similarity to previously identified B. velezensis strains. Whole-genome phylogeny using EzBiome, MiGA, and TYGS confirmed its classification as B. velezensis. Functional annotation identified genes involved in carbohydrate metabolism, including 324 carbohydrate-active enzyme (CAZyme) genes, stress response, and secondary metabolite biosynthesis. The genome also contains 50 genes associated with heavy metal resistance and plant growth promotion. Analysis using AntiSMASH identified 12 biosynthetic gene clusters involved in the production of secondary metabolites, including fengycin, surfactin, polyketides, terpenes, and bacteriocins. Notably, several clusters did not match any known sequences, suggesting the presence of potentially novel antimicrobial compounds. The genomic features of RVMD2 highlight its adaptability to extreme environments and its potential for biotechnological applications, including bioremediation and the discovery of novel bioactive metabolites.